Four Learner Categories in Global Health Experiences: A Framework for Successful Resident Engagement - Guiles, Daniel A.; Nuwagira, Edwin; Stone, Geren S. (Annals of Global Health, 2022)
An increasing number of residency programs in the United States now offer global health experiences for trainees, yet many participating residents lack the behaviors and skills needed to engage effectively with local partners and colleagues. In the experience of the authors, trainees working in global settings fall into 1 of 4 learner categories determined by their degree of cultural humility and their willingness to engage with their hosts. This viewpoint proses the concept of “re-orientation,” or ongoing structured mentorship, as a way to provide key opportunities for residents to mature in these two important areas during their global experiences. We propose that residencies should incorporate “re-orientation” as a component of their global health rotations in order to provide their trainees with the skills and behaviors to engage successfully with their local colleagues and partners.
Keywords: Global health; Medical education; Global health experience; Cultural humility